Children's Sleep Habits Questionnaire - Infant Version - Dias, Cláudia Alexandra Castro (2018)
Objectives: This study proposed a version of the Children’s Sleep Habits Questionnaire for infants under 12 months (CSHQ-I). Methods: The sample was comprised of 299 infants, aged between 2 weeks and 12 months. Results: Exploratory factor analysis revealed four subscales: Bedtime Resistance, Sleep Anxiety, Positive Sleep Habits, and Daytime Sleepiness. The CSHQ-I total scale presented good test- retest reliability and internal consistency. The CSHQ-I also showed good concurrent validity, with significant associations found between the CSHQ-I total scale and subscales and a measure of infant sleep-wake behaviors. Conclusions: The present study suggested the CSHQ-I as a reliable instrument to assess sleep problems in infants during the first year of life.